Erosive pustular dermatosis (chronic atrophic dermatosis of the scalp and extremities) - Semkova K; Tchernev G; Wollina U (Dove Medical Press, 2013)
Kristina Semkova,1 Georgi Tchernev,2 Uwe Wollina31Department of Dermatology and Venereology, Sofia Medical University, Sofia, Bulgaria; 2Policlinic for Dermatology and Venereology, Saint Kliment Ohridski University, Sofia, Bulgaria; 3Department of Dermatology and Allergology, Academic Teaching Hospital Dresden-Friedrichstadt, Dresden, GermanyAbstract: Erosive pustular dermatosis is a rare noninfectious disease of the scalp or legs. Clinical findings are nonspecific, with crusts, atrophy, and pustules. A later complication of erosive pustular dermatosis is secondary cicatrical alopecia. The list of possible differential diagnoses is long, and includes infectious, inflammatory, and neoplastic dermatoses. Treatment is challenging. Topical drug therapy may improve the condition, but rarely results in a complete resolution. Surgery has been linked to exacerbation in some patients. In our hands, it achieved complete remission in male patients.Keywords: erosive pustular dermatosis, scalp, cicatrical alopecia, leg, treatment